Global perspectives on amateur film histories and cultures - Salazkina, Masha; Fibla-Gutiérrez, Enrique (Bloomington, IN. : Indiana University Press, 2020)
"For too long, the field of amateur cinema has focused on North America and Europe. In Global Perspectives on Amateur Film Histories and Cultures, however, editors Masha Salazkina and Enrique Fibla-Gutiérrez fill the literature gap by extending that focus and increasing inclusivity. Through carefully curated essays, Salazkina and Fibla-Gutiérrez bring wider meaning and significance to the discipline through their study of alternative cinema in new territories, fueled by different historical and political circumstances, innovative technologies, and ambitious practitioners. The essays in this volume work to realize the radical societal democratization that shows up in amateur cinema around the world. In particular, diverse contributors highlight the significance of amateur filmmaking, the exhibition of amateur films, the uses and availability of film technologies, and the inventive and creative approaches of filmmakers and advocates of amateur film. Together, these essays shed new light on alternative cinema in a wide range of cities and countries where amateur films thrive in the shadow of commercial and conventional film industries"--
Includes bibliographical references and index (p. 333-336).
Keywords: Amateur films -- History and criticism